Insurance awareness and acceptance: Empirical evidence among small and medium-sized enterprises in the Lagos State, Nigeria - Sunday Stephen Ajemunigbohun; Adeoye Olarewaju Ayobami (Trends Economics and Management, 2018)
Purpose of the article: Insurance awareness in Nigeria needs to be encouraged among entrepreneurs in order to galvanise support for insurance penetration and density. Methodology/methods: A descriptive approach and survey design were employed. A singlestage cluster sampling technique and interview schedule were both employed. 352 respondents made up of small business and medium-sized operators were drawn from three Local Government Council Areas of Lagos. The statistical instruments employed for this study were the Kolmogorov-Smirnov and Kendall's rank correlation coefficient techniques. Scientific aim: This study aims at the relationship between insurance awareness and its acceptability among small business and medium-sized operators in the metropolis of Lagos. Findings: The results of this study assume that insurance products have not gained high popularity among small business and medium-sized operators in the Lagos metropolis. They have also shown that there is a low but slightly positive relationship between insurance awareness and its acceptance among small business owners in the Lagos metropolis. Our formulated hypotheses have been supported. Conclusions: This study provides a better understanding on the importance of insurance awareness as related to its acceptance among small and medium-sized entrepreneurs This study recommends that greater attention should be placed on small business owners' education of and engagement in the design of insurance products related to their activities so as to allow for the sense of ownership, effective risk management communication and proper risk financing techniques.
Keywords: G22; M31; 650; insurance awareness; insurance acceptance; risk communication; SMEs; Lagos